2014
DOI: 10.1051/epjconf/20146702101
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cavitating flow in converging-diverging nozzle based on experimental investigations

Abstract: Abstract. Cavitation phenomena occuring in converging-diverging nozzle (Venturi tube) are described in the paper. A closed test circuit with possibility to control both flow rate and static pressure level were used. Loss coefficient was evaluated for different sigma numbers resulting in full "static" characterization of the nozzle. Visualizations of the cavitation pattern development were acquired and matched with evolution of the loss coefficient. Three cavitation regimes are described: partial cavitation, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 6 publications
1
12
0
3
Order By: Relevance
“…Due to the complex mix of unsteadiness, twophase flow dynamics, turbulence and fluid-structure interactions, this is a very complicated research field. In previous research usually three different test geometries are used to visualize this cloud shedding: (1) hydrofoils ( Callenaere et al, 2001;Danlos et al, 2014;De Lange and De Bruin, 1997;Foeth et al, 2008;Long et al, 2018 ), (2) planar converging-diverging nozzles with a rectangular cross-section ("wedges") ( Chen et al, 2015;Ganesh et al, 2016;Jana et al, 2016;Croci et al, 2016 ) and (3) converging-diverging axisymmetric nozzles ("venturis") ( Rudolf et al, 2014;Hayashi and Sato, 2014;Tomov et al, 2016;Long et al, 2017 ). Although in all geometries periodic cloud shedding can be observed, due to the specific shape of each of the geometries, they all have their own characteristic flow dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex mix of unsteadiness, twophase flow dynamics, turbulence and fluid-structure interactions, this is a very complicated research field. In previous research usually three different test geometries are used to visualize this cloud shedding: (1) hydrofoils ( Callenaere et al, 2001;Danlos et al, 2014;De Lange and De Bruin, 1997;Foeth et al, 2008;Long et al, 2018 ), (2) planar converging-diverging nozzles with a rectangular cross-section ("wedges") ( Chen et al, 2015;Ganesh et al, 2016;Jana et al, 2016;Croci et al, 2016 ) and (3) converging-diverging axisymmetric nozzles ("venturis") ( Rudolf et al, 2014;Hayashi and Sato, 2014;Tomov et al, 2016;Long et al, 2017 ). Although in all geometries periodic cloud shedding can be observed, due to the specific shape of each of the geometries, they all have their own characteristic flow dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Standard orifices have one circular hole with prescribed thickness/diameter ratio and shape of the orifice edge. In our previous research [3,4], it was found out that pressure amplitudes downstream of both one-hole and multihole orifices are lower than those generated by Venturi tube.…”
Section: Introductionmentioning
confidence: 87%
“…In case of Kunz cavitation model, the source terms Re and Rc are computed using the formulas (4) and (5).…”
Section: ∂(αρ L )mentioning
confidence: 99%
“…For this purpose, cavitation and its dynamics within the Venturi tube have been investigated and results were discussed in several contributions. [5][6] [7] Introduction of swirl using the swirl generator represents the further step of this investigation. The cavitation patterns downstream the throat of the nozzle have been highly modified by the presence of the swirl.…”
Section: Introductionmentioning
confidence: 99%